EFFECT OF THE MOISTURE INCREASE IN THE TESTINGS OF DENSITY AND SATURATION DEGREE FOR MINE SOIL AT A CONSTANT SPECIFIC GRAVITY CONDITION - Deden Agus Ahmid; Bagaraja Sirait; Yayah Rohayati; Tarsono Tarsono (Indonesian Mining Journal, 2020)
The degree of density and saturation in soil sample under constant specific gravity conditions are influenced by the addition of water content. To find out its effect, it is necessary to test the samples which include compaction, moisture content, specific gravity and density testing. By recognizing the soil properties through a testing and calculation; dry density, saturation density, dry soil volume, pore volume, degree of saturation, porosity, and void ratio can be evaluated. The test shows that the optimum moisture content and dry density are 53,25% and 1.08g/cm3 respectively. The tests were conducted to five samples that have a specific gravity of 2.67. The obtained saturation degree were S-01: 79.05%, S-02: 92.40%, S-03: 95.06%, S-04: 94.64% and S-05: 93.12%. The value of water content in the five samples was S-01: 48.87%, S-02: 51.04 %, S-03: 53.25 %, S-04: 55.32 %, S-05: 57.24%. The densities in five samples were S-01: 1.50 g/cm³, S-02: 1.63 g/cm³, S-03: 1.64 g/cm³, S-04: 1.62 g/cm³, S-0 5: 1.59 g/cm³. The saturation degree will increase along with the addition of the water content and the density. However, beyond the optimum addition of the moisture content, the saturation degree will decrease in line with the density even though if the water content increase. This occurred in the constant condition of the specific gravity.